Legal And Policy Regulations for Environmental Protection in Bangladesh: A Comparison with EU Countries - Hossain, Mohammad Belayet (2022)
The multinational enterprises (MN Es) sometimes practice irresponsible behaviour in the hope of maximising their capital investment to gain more profit. Even though host countries have specific environmental laws or policies but due to desire to attract more FOi and pressure from the MNEs, some states lower their environmental standards or refrain from enforcing them. In Bangladesh, laws and policies exist to protect the environment but their standard is not high like many developed countries and significantly Jack any provision to sustainable development. This paper addresses one main question: to what extent the existing Jaws and policies of Bangladesh are compatible in order to protect environment from degradation? In this study, environmental laws of Bangladesh have been compared with few EU countries. Findings of this study show that existing environmental Jaws and policies of Bangladesh Jacks international standard and require amendments.